PELATIHAN PEMBARUAN FORMULA SEBAGAI UPAYA PENINGKATAN DAYA JUAL PRODUK SABUN CUCI TANGAN KEPADA UKM PUTAT JAYA, RT.05/RW 03 KELURAHAN PUTAT JAYA, KOTA SURABAYA (SEBAGAI UKM PERCONTOHAN PADA WILAYAH EKS. LOKALISASI) - Damaranie Dipahayu; Fitria Abbas Thalib (Jurnal Abdi Masyarakat Kita, 2021)
Usaha Kecil Menengah (UKM) Putat Jaya Surabaya focus on soap business and has not found a standardized formula to ensure product repeatability from each time of production. Pengadian kepada Masyarakat (PkM) activity by Surabaya Pharmacy Academy was expected to be able to assist these UKM to share information through training on handwash liquid soap formulations that meet SNI standards. The content of this counselling not only about soap formula with and without plant oil and their formulation but also explained how to evaluate handwash liquid soap. The result of this PkM is additional knowledge for UKM Putat Jaya about handwash liquid soap formulas that met the requirements of the SNI and information of simple evaluation that can be done independently for the repeatability production. UKM Putat Jaya have been educated about handwash liquid soap that meets SNI standart.